2018
DOI: 10.1177/0004867418788659
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of online lifestyle interventions targeting lifestyle behaviour change in depressed populations: A systematic review

Abstract: The results of this review highlight the potential of online lifestyle interventions as adjunctive treatments for depression, and the possibility of achieving significant improvements in depressive symptoms when targeting lifestyle behaviour change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 31 publications
(64 reference statements)
0
15
0
Order By: Relevance
“…257,341,342 Furthermore, a review of e-Health for people with depression found that online lifestyle interventions can have positive effects on various health behaviours, including alcohol use, sleep, and physical activity. 343 Although the current evidence base remains preliminary, mHealth shows promise for tackling the physical health disparities of people with mental illness globally, and is a promising area for future research (see Figure 1). However, adoption of mHealth will depend not only on technological advances, but also on rigorous evaluation and overcoming common limitations for digital health interventions, such as consumer perceptions (particularly around safety, reliability and trustworthiness) and ethical risks, such as the potential for intrusion, coercion, and data privacy concerns.…”
Section: Digital Technologies For People With Mental Illnessmentioning
confidence: 99%
“…257,341,342 Furthermore, a review of e-Health for people with depression found that online lifestyle interventions can have positive effects on various health behaviours, including alcohol use, sleep, and physical activity. 343 Although the current evidence base remains preliminary, mHealth shows promise for tackling the physical health disparities of people with mental illness globally, and is a promising area for future research (see Figure 1). However, adoption of mHealth will depend not only on technological advances, but also on rigorous evaluation and overcoming common limitations for digital health interventions, such as consumer perceptions (particularly around safety, reliability and trustworthiness) and ethical risks, such as the potential for intrusion, coercion, and data privacy concerns.…”
Section: Digital Technologies For People With Mental Illnessmentioning
confidence: 99%
“…Unfortunately, well-conducted multimodal lifestyle medicine studies assessing the effectiveness and feasibility of interventions for MDD are lacking; however, two case reports and a recent systematic review were published with promising, although limited results, assessing the efficacy of online-based lifestyle intervention programs to improve lifestyle behaviors in depressed individuals [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The challenge of treating depression extends to the general population where pharmacological and psychological interventions are also first-line treatments, yet have limited impact, only reducing the burden of depression by 10–30% ( 15 ). An emerging paradigm which provides a nexus between prevention, health promotion and clinical treatment of depression, is modification of known lifestyle risk factors for depression ( 16 , 17 ). In the general population, prospective studies in teenagers and adults showed that modification of lifestyle factors, including diet, exercise, weight and smoking, improved and prevented depression ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%